Hubungan Pengetahuan Remaja Tentang Gizi Dengan Kejadian Kekurangan Energi Kronik (KEK) Di MAN 1 Sleman - Elmanora, Shinta; Sulistyoningtyas, Sholaikhah (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
Low food intake or nutritional status can be caused by low nutritional knowledge and eating behavior of an adolescent so that it may result in adolescent girls experiencing CED which has an impact on disrupting the process of adolescent growth and development. This study aims to determine the relationship between knowledge level of adolescent girls about nutrition and the incidence of chronic energy deficiency (CED) in MAN (Islamic Sate High School) 1 Sleman. This research was quantitative research with correlation analysis using cross-sectional. The sampling technique applied was quota sampling technique with the sample size of 59. The research instrument used a nutritional knowledge questionnaire and Mid-Upper Arm Circumference (MUAC) band. The statistical test used was Kendall Tau-b. The results showed that the majority of female adolescents did not experience CED (61%) and had sufficient nutritional knowledge (66.1%). The results of the statistical analysis test using Kendall-tau b showed that from 59 samples a significant value (p) of 0.036 (p 0.05) was obtained, which means that the hypothesis is accepted. There is a significant relationship between the level of knowledge of adolescent girls about nutrition and the incidence of CED. increase the awareness and knowledge of nutrition through encouragement from people surround, especially family; schools; and health workers in the form of counseling on nutrition and CED. In addition, other researchers can conduct further research by adding other variables and intervene by providing counseling